Five Elements of Normative Ethics - A General Theory of Normative Individualism - von der Pfordten, Dietmar (2012)
The article tries to inquire a third way in normative ethics between consequentialism or utilitarianism and deontology or Kantianism. To find such a third way in normative ethics, one has to analyze the elements of these classical theories and to look if they are justified. In this article it is argued that an adequate normative ethics has to contain the following five elements: (1) normative individualism, i. e., the view that in the last instance moral norms and values can only be justified by reference to the individuals concerned, as its basis; (2) consideration of the individuals’ concerns and interests—aims, desires, needs, strivings—insofar as they have a justificatory function; (3) a pluralism of references of these concerns and hence of moral norms and values to all possible elements of actions; (4) the necessity of a principle of aggregation and weighing with regard to these concerns; (5) finally, as a central principle of aggregation and weighing, the principle of relative reference to self and others, operating as a generalizing meta-principle that guides the application of concrete principles and decisions.
Keywords: Plurality of the elements of action; Non-Kantianism; Non-deontology; Non-utilitarianism; Non-consequentialism; Justification of law; Justification of morals; Ethics; Normative ethics